PEMUDA : MEMILIH ATAUKAH GOLPUT DALAM PILKADA TAHUN 2015 - Hendrik Toda (Universitas Sultan Ageng Tirtayasa, 2015)
The high number of abstention in the implementation of national and local elections in Indonesia are already in an alarming stage . Indonesian young people are expected to break the deadlock that situation with no bandwagon becomes abstentions . It becomes important because the 2015 election , predicted more than 20-30 percent of young voters nationwide are among young voters . Future owners of this country is the youth . Therefore, the people's democratic party that is in sight should be exploited youth in playing its role to oversee the passage of the election , so that the election can run an honest , fair and transparent . As well as the need for support from the government to continue to encourage and empower youth in Indonesia to get involved directly in political participation